2007
DOI: 10.1108/13664380780001100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating guaranteed maximum price and target cost contracting strategies in Hong Kong construction industry

Abstract: SUMMARY• Guaranteed maximum price (GMP) and target cost contracting (TCC) with a painshare/gain-share arrangement have been adopted to integrate the construction delivery process and motivate service providers to seek continuous improvements in project outcomes. However, there is still a lack of research evidence to evaluate the levels of success and lessons learned from these innovative procurement strategies.• Based on the analysis of a series of in-depth interviews on the perceptions of various relevant exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 7 publications
0
49
0
Order By: Relevance
“…The pilot questionnaire was developed based on the risk factors documented in previous research studies by Bernhard (1988), Ahmed et al (1998), Al-Subhi Al-Harbi Kamal (1998), Ahmed et al (1999), Broome and Perry (2002), Haley and Shaw (2002), Rahman and Kumaraswamy (2002), Cheng (2004), Fan and Greenwood (2004), Oztas and Okmen (2004), Sadler (2004), Environment, Transport and Works Bureau (2005), Li et al (2005), Tang (2005), Hong Kong Housing Authority (2006), Shen et al (2006), Ng and Loosemore (2007), Chan et al (2007a), Chan et al (2007b), Yew (2008), together with seven structured interviews with experienced industrial practitioners with abundant hands-on practical experience in those TCC/GMP procurement approaches undertaken by the authors (Chan et al, 2010b). The interviewees suggested that nature of variations, change in scope of work, quality and clarity of tender documents, unforeseen ground conditions, fluctuation of materials price, and approval from regulatory bodies for alternative cost saving designs were the key risk factors associated with TCC/GMP contracts in Hong Kong.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The pilot questionnaire was developed based on the risk factors documented in previous research studies by Bernhard (1988), Ahmed et al (1998), Al-Subhi Al-Harbi Kamal (1998), Ahmed et al (1999), Broome and Perry (2002), Haley and Shaw (2002), Rahman and Kumaraswamy (2002), Cheng (2004), Fan and Greenwood (2004), Oztas and Okmen (2004), Sadler (2004), Environment, Transport and Works Bureau (2005), Li et al (2005), Tang (2005), Hong Kong Housing Authority (2006), Shen et al (2006), Ng and Loosemore (2007), Chan et al (2007a), Chan et al (2007b), Yew (2008), together with seven structured interviews with experienced industrial practitioners with abundant hands-on practical experience in those TCC/GMP procurement approaches undertaken by the authors (Chan et al, 2010b). The interviewees suggested that nature of variations, change in scope of work, quality and clarity of tender documents, unforeseen ground conditions, fluctuation of materials price, and approval from regulatory bodies for alternative cost saving designs were the key risk factors associated with TCC/GMP contracts in Hong Kong.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The net cost adjustment of such GMP/TCC variations will be added to (for 'addition' work) or subtracted from (for 'omission' work) the contract GMP or target cost. Chan et al (2007a) further summarised the key characteristics in relation to the GMP/TCC procurement strategy as follows:…”
Section: Features Of Gmp/tcc Contractsmentioning
confidence: 99%
“…Chan et al (2007b) opined that inexperienced clients and contractors may jeopardise the TCC/GMP process. This risk appears to be inevitable in Hong Kong, since the number of TCC/GMP projects completed is rather scarce in the local construction market.…”
Section: Risks To Be Shared Between Client and Contractormentioning
confidence: 99%